Methanation catalyst and preparation method and application thereof
By reducing the precursor to amorphous nickel in the preparation process of the methanation catalyst using a reducing agent and mixing it with the support and cellulose, the problem of pre-activated reduction of the catalyst is solved, the efficiency of the methanation reaction is improved, and the carbon dioxide content in methane products is reduced.
Patent Information
- Application Number
- CN202111432754.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-11-29
AI Technical Summary
The existing methanation catalysts require pre-activated reduction, but the temperature of isothermal methanation reactors does not easily meet the reduction conditions, and the carbon monoxide and carbon dioxide content in the methane product gas is still relatively high.
The precursor I and precursor II were reduced by reducing agent to obtain amorphous nickel as active components, and mixed with the support and cellulose, and the methanation catalyst obtained by calcination without further reduction.
The hydrogenation capacity of the catalyst is improved, the carbon monoxide and carbon dioxide content in the methane product gas is reduced, and the carbon dioxide content is suitable for isothermal reactors, and the carbon dioxide content is reduced to below 100ppm in a single-stage isothermal reactor.
Smart Images

Figure CN116173969B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of methanation catalysts, and in particular to a methanation catalyst and a preparation method and application thereof. Background Art
[0002] The bottleneck of syngas methanation technology is to improve the conversion rate of carbon dioxide. Since the methanation rate of carbon monoxide is much higher than that of carbon dioxide, methane products usually contain a large amount of carbon dioxide. When the carbon dioxide content is too high, the methane product will not meet the national standard of SNG methane content greater than 96%, or additional separation equipment will be needed to separate and purify SNG.
[0003] The first generation of methanation reaction represented by adiabatic reactors has the characteristics of long process flow, multiple equipments and high reaction temperature. It has high requirements on investment amount, operation control, product quality, catalyst life and many other factors. Normally, when carbon monoxide and carbon dioxide coexist in the synthesis gas, the reaction temperature reaches 600℃ and carbon dioxide will no longer be converted. If the temperature continues to rise, part of carbon monoxide will be converted into carbon dioxide, making the carbon dioxide conversion rate negative.
[0004] The methanation reaction is a highly exothermic reaction with reduced volume. The second generation of methanation reaction represented by isothermal reactors uses a lower reaction temperature to improve the balance of the methanation reaction. The isothermal reactor is usually used as a subsequent refining section of the adiabatic reactor to reduce the residual carbon monoxide and carbon dioxide in the outlet product of the adiabatic reactor. Although the use of an isothermal reactor for refining can reduce the residual carbon monoxide and carbon dioxide content in the adiabatic product gas, the existing methanation catalyst still has problems such as poor heat and mass transfer performance, poor stability, and low carbon dioxide conversion rate during the isothermal methanation process, resulting in a high carbon dioxide content in the methane product. In addition, the existing methanation catalyst needs to be pre-activated and reduced before use so that the precursor of the active component is reduced to a catalytically active metal, and the temperature of the isothermal reactor is not easy to meet the reduction conditions. Therefore, an additional activation and reduction process needs to be added before the isothermal methanation reaction, which makes the cost and energy consumption higher.
[0005] CN113499763A discloses a coke oven gas isothermal methanation catalyst and a preparation method thereof, wherein the catalyst contains 60-80% of a carrier, 15-35% of an active component and 1-5% of an auxiliary agent by weight of the catalyst, wherein the carrier is a composite oxide formed by aluminum and magnesium, and the auxiliary agent is a mixture of one or more oxides of Ce, Zr, Mo, Mn and La. The method uses an impregnation method to load a precursor of the active component nickel on a specific aluminum and magnesium composite oxide carrier, and then performs drying, roasting and pre-activation reduction before use. Although the obtained catalyst has a high conversion rate of carbon dioxide, the active component in the catalyst is crystalline nickel, and its hydrogenation ability for carbon dioxide is not as good as that of amorphous nickel, so that the content of carbon dioxide in the methane product is still high, and the catalyst also needs to be pre-activated and reduced before use, and the cost and energy consumption are higher. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem that the existing methanation catalyst needs to be pre-activated and reduced, but the temperature of the isothermal methanation reactor is not easy to meet the reduction conditions, and the contents of carbon monoxide and carbon dioxide in the methane product gas are still high. A methanation catalyst and a preparation method and application thereof are provided. The methanation catalyst does not need to be reduced and is beneficial to reducing the contents of carbon monoxide and carbon dioxide in the methane product gas.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a methanation catalyst, the method comprising:
[0008] (1) in the presence of a first solvent, contacting the precursor I and the precursor II with a reducing agent to perform a reduction reaction to obtain a reduction product;
[0009] (2) mixing the reduced product with a carrier and cellulose in the presence of a second solvent to obtain a suspension;
[0010] (3) removing the second solvent from the suspension, and then calcining the obtained solid under an inert atmosphere to obtain a methanation catalyst;
[0011] Wherein, the precursor I is a compound containing nickel, and the precursor II is selected from compounds containing lanthanum and / or cerium.
[0012] The second aspect of the present invention provides a methanation catalyst prepared by the method described in the first aspect, the methanation catalyst comprising a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is amorphous nickel and the auxiliary agent is selected from oxides of La and / or Ce.
[0013] The third aspect of the present invention provides use of the methanation catalyst described in the second aspect in preparing natural gas by methanation reaction.
[0014] Through the above technical scheme, the method for preparing a methanation catalyst provided by the present invention improves the traditional method for preparing a methanation catalyst, uses a reducing agent to reduce precursor I and precursor II, then mixes the reduced product with a carrier and cellulose, finally removes the second solvent in the suspension, and calcines under an inert atmosphere. The prepared methanation catalyst includes a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is amorphous nickel, and the auxiliary agent is selected from La and / or Ce oxides. The active component in the methanation catalyst is amorphous nickel. Compared with the catalyst whose active component is crystalline nickel, the methanation catalyst improves the hydrogenation capacity of the active component, so that carbon dioxide with a slower methanation reaction rate can proceed faster in the positive direction of the reaction. In addition, the methanation catalyst itself is in a reduced state, and does not need to be reduced before use. It is more suitable for isothermal reactors, and when the synthesis gas is not higher than 15000h -1 At a volume space velocity of 100 ppm and a total carbon load of no more than 10 vol%, the carbon dioxide content in the methane product gas can be reduced to below 100 ppm by a single-stage isothermal reactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the XRD pattern of the methanation catalyst prepared in Example 8. DETAILED DESCRIPTION
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0017] A first aspect of the present invention provides a method for preparing a methanation catalyst, the method comprising:
[0018] (1) in the presence of a first solvent, contacting the precursor I and the precursor II with a reducing agent to perform a reduction reaction to obtain a reduction product;
[0019] (2) mixing the reduced product with a carrier and cellulose in the presence of a second solvent to obtain a suspension;
[0020] (3) removing the second solvent from the suspension, and then calcining the obtained solid under an inert atmosphere to obtain a methanation catalyst;
[0021] Wherein, the precursor I is a compound containing nickel, and the precursor II is selected from compounds containing lanthanum and / or cerium.
[0022] According to some embodiments of the present invention, in step (1), in the presence of a first solvent, the precursor I and the precursor II are contacted with a reducing agent to perform a reduction reaction to obtain a reduced product. This step can reduce the nickel element in the precursor I and the precursor II to metal, and finally obtain a reduced product containing amorphous elemental nickel and lanthanum and / or cerium hydroxide in the solution. The present invention does not particularly limit the type of the reducing agent, and can be a conventional choice in the art, as long as the nickel element in the precursor I can be reduced to amorphous nickel. Preferably, the reducing agent is a borohydride, more preferably sodium borohydride and / or potassium borohydride.
[0023] According to some embodiments of the present invention, the precursor I is a compound containing nickel. There is no particular limitation on the type of the precursor I, which can be a conventional choice in the art, for example, a conventional water-soluble nickel salt in the art. Preferably, the precursor I is selected from at least one of nickel nitrate, nickel chloride and nickel acetate, more preferably nickel nitrate.
[0024] According to some embodiments of the present invention, the precursor II is selected from compounds containing lanthanum and / or cerium. There is no particular limitation on the type of the precursor II, which can be a conventional choice in the art, for example, a conventional water-soluble lanthanum salt and / or a water-soluble cerium salt in the art. Preferably, the precursor II is selected from nitrates and / or chlorides containing lanthanum and / or cerium, more preferably nitrates containing lanthanum and / or cerium.
[0025] According to some embodiments of the present invention, preferably, in terms of metal elements, the mass ratio of the precursor I to the precursor II is (20-110): 1, more preferably (20-100): 1. The above preferred embodiments are conducive to further reducing the content of carbon monoxide and carbon dioxide in the methane product gas.
[0026] According to some embodiments of the present invention, preferably, the molar ratio of the reducing agent to the total amount of the precursor I and the precursor II calculated as metal elements is (1-2.5): 1, preferably (1.5-2): 1. The above preferred embodiments can further promote the formation of amorphous nickel particles and lanthanum and / or cerium hydroxides by chemical reduction.
[0027] According to some embodiments of the present invention, preferably, the first solvent is water.
[0028] According to some embodiments of the present invention, preferably, the precursor I, precursor II and reducing agent are provided in the form of a solution. There is no particular limitation on the order of adding the precursor I, precursor II and reducing agent, and they can be mixed in any order. Preferably, the precursor I and the precursor II are first dissolved in water, and then contacted with a solution containing a reducing agent for reduction reaction. More preferably, the mixed solution containing the precursor I and the precursor II is dripped into the solution containing the reducing agent in a dropwise manner for contact, and the dripping speed can be 4-6 drops / second. Further preferably, in the solution containing the reducing agent, the concentration of the reducing agent is 1-3mol / L; in the mixed solution containing the precursor I and the precursor II, the concentration of the precursor I and the precursor II is 0.5-2mol / L.
[0029] According to some embodiments of the present invention, preferably, the conditions of the reduction reaction include: a temperature of 15-25° C. and a time of 1-3 h. In order to remove oxygen from the solution, further promote the formation of the reduction product, and improve the dispersion of the reduction product, more preferably, the reduction reaction is carried out under high-frequency oscillation. The conditions and methods of the high-frequency oscillation can be conventionally selected in the art and are not particularly limited thereto.
[0030] According to some embodiments of the present invention, in order to better precipitate and separate the reduction product, preferably, a magnetic substance or device may be used during the reduction reaction to assist in the precipitation of the reduction product.
[0031] According to some embodiments of the present invention, preferably, the method further comprises subjecting the reduction product obtained in step (1) to solid-liquid separation and washing. The present invention does not particularly limit the method of solid-liquid separation, and it can be a conventional choice in the art, for example, it can be at least one of filtration, centrifugal separation and gravity sedimentation, preferably, solid-liquid separation is performed by centrifugation to remove the supernatant. The washing can be performed using a washing liquid conventionally used in the art, such as deionized water. Preferably, washing is performed by repeatedly adding deionized water and removing the supernatant until the washing liquid is neutral.
[0032] According to some embodiments of the present invention, in step (2), in the presence of a second solvent, the reduced product is mixed with a carrier and cellulose to obtain a suspension. This step can load the amorphous nickel in the reduced product and the hydroxide of lanthanum and / or cerium on the carrier. The cellulose can not only play the role of thickening and pore-forming, but also fully mix the carrier with the reduced product, and will not cause precipitation and stratification due to different particle settling speeds, promote the dispersion of amorphous nickel and the hydroxide of lanthanum and / or cerium on the carrier, so as to further improve the catalytic activity of the catalyst. At the same time, the adhesion between the amorphous nickel and the hydroxide of lanthanum and / or cerium in the reduced product and the carrier can also be increased to make it more closely combined. Preferably, the second solvent is water. More preferably, the mixing process can be carried out under stirring. The stirring conditions and methods can be conventionally selected in the art, and there is no particular limitation on this. Further preferably, the stirring is carried out using non-ferromagnetic equipment.
[0033] According to some embodiments of the present invention, the carrier can be a carrier suitable for supported catalysts conventionally used in the art, as long as it can support amorphous nickel and hydroxides and / or oxides of lanthanum and / or cerium, the purpose of the present invention can be achieved to a certain extent. Preferably, the carrier is selected from at least one of alumina, zirconia and magnesium aluminum spinel.
[0034] According to some embodiments of the present invention, preferably, the mass ratio of the precursor I to the carrier in terms of metal element is (0.1-1.5): 1, preferably (0.176-1): 1. The above preferred embodiments are conducive to further improving the dispersion of amorphous nickel on the carrier, so that the methanation catalyst has a certain microscopic morphology, while providing a reaction environment of different acidity when the catalyst is methanated, and fully supporting the active components and additives, thereby increasing the contact area between the catalyst and the airflow diffusion.
[0035] According to some embodiments of the present invention, preferably, the mass ratio of the cellulose to the second solvent is (0.5-1.5): 100, preferably (0.8-1.2): 100. The above preferred embodiments are conducive to further promoting uniform mixing of the reduction product and the carrier, and further improving the adhesion of the amorphous nickel and lanthanum and / or cerium hydroxides on the carrier.
[0036] According to some embodiments of the present invention, in step (3), the second solvent in the suspension is removed, and then the obtained solid is calcined under an inert atmosphere to obtain a methanation catalyst. The step can convert the hydroxide of lanthanum and / or cerium supported on the carrier into an oxide of lanthanum and / or cerium. Preferably, the second solvent in the suspension can be removed by drying. The drying conditions and methods can be conventionally selected in the art and are not particularly limited thereto.
[0037] According to some embodiments of the present invention, preferably, the calcination conditions include: a heating rate of 1-5°C / min, preferably 2-4°C / min; a temperature of 300-400°C, preferably 330-350°C; and a time of 1-10h, preferably 2-5h.
[0038] According to some embodiments of the present invention, preferably, the method is carried out under an inert atmosphere.
[0039] According to some embodiments of the present invention, preferably, the inert atmosphere is provided by at least one of nitrogen, argon, helium and neon.
[0040] According to some embodiments of the present invention, preferably, the method further comprises crushing and molding the methanation catalyst obtained in step (3) so that the methanation catalyst has a certain strength and morphology. More preferably, the crushing and molding are completed within 1 hour after completing step (3) to obtain a molded catalyst product. In order to prevent the molded catalyst product from being oxidized, it is preferably stored in a sealed state under an inert atmosphere.
[0041] The second aspect of the present invention provides a methanation catalyst prepared by the method described in the first aspect, the methanation catalyst comprising a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is amorphous nickel and the auxiliary agent is selected from oxides of La and / or Ce.
[0042] According to some embodiments of the present invention, the active component in the methanation catalyst is amorphous nickel, which has a stronger hydrogenation capacity. Preferably, in the XRD spectrum of the methanation catalyst, there is a broad diffraction peak with a peak width greater than 5° at 2θ=45°. The broad diffraction peak is a diffuse peak type formed by amorphous diffuse reflection, which is the main characteristic diffraction peak of amorphous nickel. The short and wide diffuse peak indicates that the nickel in the methanation catalyst exists in an amorphous structure.
[0043] According to some embodiments of the present invention, the type of the carrier can be selected with reference to the above, and will not be described in detail here.
[0044] According to some embodiments of the present invention, preferably, based on the total weight of the methanation catalyst, the content of the active component is 10-55% by weight, the content of the auxiliary agent is 0.3-2% by weight, and the content of the carrier is 40-90% by weight;
[0045] More preferably, based on the total weight of the methanation catalyst, the content of the active component is 15-50% by weight, the content of the auxiliary agent is 0.35-1.7% by weight, and the content of the carrier is 45-85% by weight.
[0046] The third aspect of the present invention provides use of the methanation catalyst described in the second aspect in preparing natural gas by methanation reaction.
[0047] According to some embodiments of the present invention, preferably, the methanation catalyst is used at a temperature of not more than 15000 h -1 At a volume space velocity of 100 ppm and a total carbon load of no more than 10 vol%, the carbon dioxide content in the methane product gas can be reduced to below 100 ppm by a single-stage isothermal reactor.
[0048] The present invention will be described in detail below through examples.
[0049] In the following examples and comparative examples, unless otherwise specified, the raw materials used are commercially available products.
[0050] The composition of the catalyst was determined by a ZSX Primus II X-ray fluorescence spectrometer (XRF) from Rigaku;
[0051] The XRD spectrum of the catalyst was measured by an X-ray diffractometer. The powder X-ray diffractometer was purchased from Bruker Company and its model was D8 advance.
[0052] Examples 1-8 are used to illustrate the methanation catalyst and preparation method thereof provided by the present invention.
[0053] Example 1
[0054] 200 g of nickel nitrate pentahydrate was dissolved in 500 mL of deionized water, and 1.01 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:1). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 1.5:1) at a rate of 4 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 2 hours), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The supernatant was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 80.27g of alumina powder (the mass ratio of nickel to alumina was 0.54:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 5g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 1:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 3°C / min, calcined at 350°C for 4 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 1. Among them, the content of nickel was 35% by weight, the content of lanthanum in terms of oxide was 0.35% by weight, and the content of aluminum oxide was 64.65% by weight.
[0055] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0056] Example 2
[0057] 200 g of nickel nitrate pentahydrate was dissolved in 300 mL of deionized water, and 1.01 g of cerium nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to cerium element was 100:1). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and cerium elements was 2:1) at a rate of 4 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 1 hour), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The supernatant was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 80.27g of alumina powder (the mass ratio of nickel element to alumina was 0.54:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 6g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 1.2:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 4°C / min, calcined at 330°C for 2 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 2. Among them, the nickel content was 35% by weight, the cerium content in terms of oxide was 0.35% by weight, and the aluminum oxide content was 64.65% by weight.
[0058] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0059] Example 3
[0060] 200 g of nickel nitrate pentahydrate was dissolved in 400 mL of deionized water, and 5.05 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:5). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 1.7:1) at a rate of 6 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 2 hours), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The supernatant was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 80.27g of alumina powder (the mass ratio of nickel to alumina was 0.54:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 4g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 0.8:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 2°C / min, calcined at 340°C for 3 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 3. Among them, the content of nickel was 34% by weight, the content of lanthanum in terms of oxide was 1.7% by weight, and the content of aluminum oxide was 64.3% by weight.
[0061] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0062] Example 4
[0063] 200 g of nickel nitrate pentahydrate was dissolved in 500 mL of deionized water, and 3.03 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:3). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 1.5:1) at a rate of 5 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 3 hours), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The supernatant was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 244.93g of alumina powder (the mass ratio of nickel to alumina was 0.176:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 5g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 1:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 4°C / min, calcined at 350°C for 4 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 4. Among them, the content of nickel was 15% by weight, the content of lanthanum in terms of oxide was 0.45% by weight, and the content of aluminum oxide was 84.55% by weight.
[0064] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0065] Example 5
[0066] 200 g of nickel nitrate pentahydrate was dissolved in 500 mL of deionized water, and 3.03 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:3). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 1.5:1) at a rate of 6 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 2 hours), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The supernatant was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 43.22g of alumina powder (the mass ratio of nickel to alumina was 1:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 5g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 1:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 3°C / min, calcined at 330°C for 4 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 5. Among them, the content of nickel was 49% by weight, the content of lanthanum in terms of oxide was 1.5% by weight, and the content of aluminum oxide was 49.5% by weight.
[0067] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0068] Example 6
[0069] 200 g of nickel nitrate pentahydrate was dissolved in 600 mL of deionized water, and 1.01 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:1). The mixed solution was dripped into a 1.6 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 1.8:1) at a rate of 4 drops / second, the solution temperature was maintained at 20℃±2℃, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the entire reduction process took 3 hours), the product was allowed to precipitate freely, and magnetic substances were used to assist precipitation at the bottom. The upper clear liquid was skimmed off, and deionized water was added to wash the precipitate several times until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500 mL, 80.27 g of zirconium oxide powder (the mass ratio of nickel to zirconium oxide was 0.54:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, and 6 g of cellulose (the mass ratio of cellulose to deionized water above the precipitate was 1.2:100) was added, and stirring was continued to make all powdered substances uniformly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in a 60℃ oven, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to heat at a rate of 2°C / min, calcined at 330°C for 2 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as sample 6. Among them, the content of nickel was 34% by weight, the content of lanthanum in terms of oxide was 1.1% by weight, and the content of zirconium oxide was 64.9% by weight.
[0070] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0071] Example 7
[0072] 200 g of nickel nitrate pentahydrate was dissolved in 400 mL of deionized water, and 1.01 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:1). The mixed solution was dripped into a 1.5 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 2:1) at a rate of 6 drops / second, the solution temperature was maintained at 20°C±2°C, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the time of the entire reduction process was 1 hour), the product was allowed to precipitate freely, and a magnetic substance was used below to assist precipitation. The precipitate was washed several times by skimming off the upper clear liquid and adding deionized water until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500 mL, 80.27 g of magnesia-alumina spinel powder (the mass ratio of nickel to magnesia-alumina spinel was 0.54:1) was added, and non-ferromagnetic equipment was used to stir for 1 minute, 6 g of cellulose was added (the mass ratio of cellulose to the deionized water above the precipitate was 1.2:100), and stirring was continued to make all powdery substances evenly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in an oven at 60°C, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to rise in temperature at a rate of 2°C / min, and calcined at 350°C for 3 hours, then cooled to room temperature. The cooled block was broken in a sealed bag, and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as Sample 7. Among them, the nickel content was 34.65% by weight, the lanthanum content in terms of oxide was 0.35% by weight, and the magnesium aluminum spinel content was 65% by weight.
[0073] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0074] Example 8
[0075] 200 g of nickel nitrate pentahydrate was dissolved in 500 mL of deionized water, and 3.03 g of lanthanum nitrate was added to prepare a mixed solution (wherein the mass ratio of nickel element to lanthanum element was 100:3). The mixed solution was dripped into a 2 mol / L sodium borohydride solution (the molar ratio of sodium borohydride to the total amount of nickel and lanthanum was 2:1) at a rate of 4 drops / second, the solution temperature was maintained at 20°C ± 2°C, high-frequency oscillation was turned on, and the black substance produced during the dripping process was dispersed. After the dripping was completed (the time of the entire reduction process was 2h), the product was allowed to precipitate freely, and a magnetic substance was used below to assist precipitation. The precipitate was washed several times by skimming off the upper clear liquid and adding deionized water until the solution was neutral. The amount of deionized water above the precipitate was controlled to about 500mL, 40.13g of alumina powder and 40.13g of zirconium oxide powder were added (the mass ratio of nickel element to the total amount of dual carriers was 0.54:1), and non-ferromagnetic equipment was used to stir for 1min, 5g of cellulose was added (the mass of cellulose to the deionized water above the precipitate was 1:100), and stirring was continued to make all powdery substances evenly distributed and suspended in the viscous liquid to obtain a suspension. The suspension was placed in an oven at 60°C, and the water was evaporated under nitrogen protection until it was dried. The dried block was placed in a sealed bag and crushed, taken out and placed in a muffle furnace, protected by argon, and programmed to rise in temperature at a rate of 3°C / min, calcined at 350°C for 4 hours, and then cooled to room temperature. The cooled block was broken in a sealed bag and formed into φ4*4 cylindrical tablets within 1 hour to obtain a methanation catalyst, which was sealed and filled with nitrogen and recorded as Sample 8. Among them, the nickel content was 34.65% by weight, the lanthanum content in terms of oxide was 0.35% by weight, and the total content of the dual carriers (alumina and zirconium oxide) was 65% by weight.
[0076] The XRD spectrum of the methanation catalyst is shown in Figure 1 As shown in the figure, it can be seen that at 2θ=45°, there is an obvious broad diffraction peak with a peak width greater than 5°, and the broad diffraction peak is the main characteristic diffraction peak of amorphous nickel. The short and wide diffusion peak indicates that the nickel in the methanation catalyst exists in an amorphous structure, that is, the active component nickel in the methanation catalyst is amorphous nickel.
[0077] Comparative Example 1
[0078] The same precursor as in Example 1 was used, and alumina powder was used as the carrier raw material. Alumina powder was prepared into a φ4*4 carrier by a conventional molding method. 100g of the carrier was excessively impregnated with a nickel nitrate solution of ρ=1.6g / mL for 2h, dried at 120°C for 6h, and roasted at 400°C for 4h. The above impregnation, drying, and roasting methods were repeated for a second impregnation. After two impregnations and two roastings, the nickel oxide increment on 100g of the carrier was 68.44g. Then, according to the water absorption rate, an equal volume of the solute was impregnated with a solution of 2.93g lanthanum nitrate, dried at 120°C for 6h, roasted at 450°C for 4h, and pre-reduced with pure hydrogen at 450°C for 6h to obtain a methanation catalyst, which was recorded as D1. Among them, the nickel content was 35% by weight, the lanthanum content was 0.35% by weight in terms of oxide, and the aluminum oxide content was 64.65% by weight.
[0079] XRD detection shows that the active component nickel in the methanation catalyst is crystalline nickel.
[0080] Comparative Example 2
[0081] According to the method of Example 1, except that cellulose was not added during the preparation of the methanation catalyst, the other raw materials, steps, conditions, etc. were the same as those of Example 1, and a methanation catalyst was obtained, which was recorded as D2. Among them, the content of nickel was 35% by weight, the content of lanthanum in terms of oxide was 0.35% by weight, and the content of aluminum oxide was 64.65% by weight.
[0082] XRD detection shows that the active component nickel in the methanation catalyst is amorphous nickel.
[0083] Test Case
[0084] Samples 1-8 and D1-D2 were loaded into an isothermal bed reactor in an amount of 50 mL, respectively. Under single-stage isothermal non-circulating reaction process conditions (volume space velocity see Table 1, inlet temperature is 260°C, pressure is 3.0 MPa), synthesis gas (v / v composition: CO 0-5%, CO2 5-10%, H2 55-60%, CH4 30-35%) was subjected to methanation reaction, and the reaction temperature was controlled below 350°C. The obtained methane product was subjected to performance test and analysis. The results are shown in Table 1.
[0085] Table 1
[0086]
[0087]
[0088] Note: Total carbon load is the total volume content of carbon oxides (CO and CO2) in the synthesis gas; CO2 load is the volume content of CO2 in the synthesis gas; residual CO content is the CO content in the methane product gas, and residual CO2 content is the CO2 content in the methane product gas.
[0089] It can be seen from the above results that the methanation catalyst prepared by the method of the present invention is in a reduced state and does not need to be reduced before use. It is more suitable for isothermal reactors and can be used in a syngas reactor at a temperature of no more than 15000 h. -1 At a volume space velocity of 100 ppm and a total carbon load of no more than 10 vol%, the carbon dioxide content in the methane product can be reduced to below 100 ppm by a single-stage isothermal reactor.
[0090] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a methanation catalyst, characterized in that: The method comprises the following steps: (1) in the presence of a first solvent, contacting the precursor I and the precursor II with a reducing agent to perform a reduction reaction to obtain a reduction product; (2) mixing the reduced product with a carrier and cellulose in the presence of a second solvent to obtain a suspension; (3) removing the second solvent from the suspension, and then calcining the obtained solid under an inert atmosphere to obtain a methanation catalyst; Wherein, the precursor I is a compound containing nickel, and the precursor II is selected from compounds containing lanthanum and / or cerium; In step (3), the calcination conditions include: a heating rate of 1-5°C / min, a temperature of 300-350°C, and a time of 1-10h; The methanation catalyst prepared by the method comprises a carrier and an active component and an auxiliary agent supported on the carrier, wherein the active component is amorphous nickel, and the auxiliary agent is selected from La oxide and / or Ce oxide.
2. The method according to claim 1, wherein: In step (1), the reducing agent is a borohydride; and / or the precursor I is selected from nickel nitrate and nickel acetate; and / or the precursor II is selected from nitrates containing lanthanum and / or cerium.
3. The method according to claim 1, wherein: Calculated in terms of metal elements, the mass ratio of the precursor I to the precursor II is (20-110): 1; and / or, the molar ratio of the reducing agent to the total amount of the precursor I and the precursor II calculated as metal elements is (1-2.5):1; and / or, the precursor I, precursor II and reducing agent are provided in the form of a solution; And / or, the reduction reaction conditions include: temperature of 15-25° C. and time of 1-3 h.
4. The method according to claim 3, wherein: Calculated in terms of metal elements, the mass ratio of the precursor I to the precursor II is (20-100): 1; And / or, the molar ratio of the reducing agent to the total amount of the precursor I and the precursor II calculated as metal elements is (1.5-2):
1.
5. The method according to claim 1, wherein: In step (2), the carrier is selected from at least one of alumina, zirconium oxide and magnesium aluminum spinel; and / or The mass ratio of the precursor I to the carrier, calculated as the metal element, is (0.1-1.5): 1; and / or The mass ratio of the cellulose to the second solvent is (0.5-1.5):
100.
6. The method according to claim 5, wherein: In step (2), the mass ratio of the precursor I to the carrier, calculated as the metal element, is (0.176-1):1; and / or The mass ratio of the cellulose to the second solvent is (0.8-1.2):
100.
7. The method according to claim 1, wherein: In step (3), the calcination conditions include: a heating rate of 2-4°C / min; a temperature of 330-350°C; and a calcination time of 2-5h; And / or, the inert atmosphere is provided by at least one of nitrogen, argon, helium and neon.
8. The method according to any one of claims 1 to 7, wherein: The first solvent and the second solvent are both water; and / or, the method further comprises performing solid-liquid separation and washing on the reduction product.
9. The method according to claim 8, wherein: The method is carried out under an inert atmosphere.
10. A methanation catalyst prepared by the method according to any one of claims 1 to 9, characterized in that: The methanation catalyst comprises a carrier, an active component and an auxiliary agent supported on the carrier, wherein the active component is amorphous nickel, and the auxiliary agent is selected from La oxide and / or Ce oxide.
11. The methanation catalyst according to claim 10, wherein In the XRD spectrum of the methanation catalyst, there is a broad diffraction peak with a peak width greater than 5° at 2θ=45°.
12. The methanation catalyst according to claim 10 or 11, wherein Based on the total weight of the methanation catalyst, the content of the active component is 10-55% by weight, the content of the auxiliary agent is 0.3-2% by weight, and the content of the carrier is 40-90% by weight; The sum of the contents of the components in the methanation catalyst is 100% by weight.
13. The methanation catalyst according to claim 12, wherein Based on the total weight of the methanation catalyst, the content of the active component is 15-50% by weight, the content of the auxiliary agent is 0.35-1.7% by weight, and the content of the carrier is 45-85% by weight; The sum of the contents of the components in the methanation catalyst is 100% by weight.
14. Use of the methanation catalyst according to any one of claims 10 to 13 in preparing natural gas by methanation reaction.
Citation Information
Patent Citations
filter press
CH43035A
Coke-oven gas isothermal methanation catalyst and preparation method thereof
CN113499763A
Synthesis gas methanation catalyst preparation method
CN106944061A